Macroscopic, Microscopic, and Paleo-depositional Features of selected Coals in Arahan, Banjarsari, Subanjeriji, and South Banko Regions, South Sumatra - Nana Suwarna; Y. Kusumahbrata (Geological Agency, 2010)
DOI: 10.17014/ijog.v5i4.110The Arahan, Banjarsari, Subanjeriji, and Banko Regions, parts of the Bukit Asam coalfield, is situated in the Lematang Depression of South Palembang Sub-basin, South Sumatera Basin. Twenty two fresh outcrop and subcrop samples of Seam B, A, Benuang, Enim, and Jelawatan of the Mio-Pliocene Muaraenim coals have been analyzed macroscopically and microscopically, to assess the characteristics and depositional environment of the coal present. On the basis of lithotype analysis, accompanied by organic-petrological and SEM analyses, the coal seams of the Muaraenim Formation show variations in the predominance of some macerals, indicating successions of environmental changes. Petrographically, the dominant maceral group is vitrinite, present in high to very high values (69.4 – 97.4 %); whilst the minor one is inertinite showing a low to moderate amount (0.4 – 22.0 %), followed by low to moderate value of exinite (0.4 – 18.2 %). Vitrinite reflectance values are present in a low to moderate level, varying from 0.34 to 0.55 %, with one sample showing value of 0.59 %. Mineral matter dominated by clay minerals, with minor pyrite and carbonate, displays a low degree (0.4 – 5.4 %), with one sample of 12.0 %. Organic facies study tends to indicate that the coals were deposited in a wet forest swamp to limnic zone, within lower delta plain to transgressive area. This condition has supported the depositional setting interpreted from sedimentary facies associations that shows a shallow-water continental margin sequence, varying from a fluvial to deltaic environment. The organic facies concept is thus applicable in basin studies context and has potential to become an additional tool for interpretation of depositional environment.